PEMANFAATAN MEDIA KOMUNIKASI UNTUK MENGEDUKASI MASYARAKAT TENTANG CARA MENGELOLA SAMPAH DI KOTA YOGYAKARTA - Raden Roro Antonia Nismara Paramesti; Dhimas Ilham Bintang Pratama; Fijannatin Naim (Program Studi Ilmu Komunikasi Universitas Mataram, 2023)
This research discusses the use of communication media as an effective means of educating the public on how to manage household waste properly and correctly. Education on how to manage waste to the public through various communication media is considered very important because currently, especially the Special Region of Yogyakarta, has a waste emergency status which has very bad consequences for the environment. This research uses a qualitative descriptive method and takes a case study at the Nitikan Reduce Reuse Recycle Waste Management Site (TPS3R Nitikan). Data is collected with interview, observation and documentation technique. This research shows that the usage of banner, poster and leaflet is less effective because of lack of the numbers and distributions. On the other hand, education and training are better because they provide interaction between trainers and participants. Next, Instagram and YouTube are considered more efficient because they can reach more people and wider area. They can also be accessed and shared easily at any time. In order to enhance the number of viewers, Environmental Office of Yogyakarta which is responsible for handling the waste management need to add the frequency and vary the content of Instagram and YouTube exposing the existence of TPS3R Nitikan and its program called “Laron Sarungan/Urban Household Waste Processing Laboratory”.